Management Styles' Levels of Predicting Job Satisfaction and Burnout: Intermediary Role of Organizational Justice - Alanoglu, Muslim; Demirtas, Zulfu (Turkish Education Assoc, 2020)
The purpose of the present study is to find out the intermediary role of organizational justice on the effects of perceived principal management styles on teachers' job satisfaction and burnout levels. It was designed as relational survey model, predictive design research model was used. The universe of the study consists of 3194 teachers working in Mersin city centre during the 2017-2018 academic year and 561 teachers from this universe were taken to the sample through simple random sampling method. Perceived-Principal Management Style, Organizational Justice, Teaching Job Satisfaction and Maslach Burnout Scales were used to collect to data. Following the data collection, mediation analyses were performed with the help of data collected by using structural equation model. It was found that organizational justice was a complete mediating variable in cooperative management style's predicting job satisfaction, while it was found to be a partial mediating variable in predicting emotional exhaustion and it was not found to have any mediating role in cooperative management style's predicting personal achievement and depersonalization. Organizational justice was a partial mediating variable in authoritative management style's predicting emotional exhaustion, while it was not found to have any mediating role in authoritative management style's predicting job satisfaction, personal achievement and depersonalization. Organizational justice was also a partial mediating variable in indifferent management style's predicting job satisfaction and emotional exhaustion, while it was not found to have any mediating role in indifferent management style's predicting personal achievement and depersonalization. It was also found that organizational justice did not have a mediating variable effect in resistant management style's predicting job satisfaction, emotional exhaustion, personal achievement and depersonalization. Finally, the relevant results were discussed in the literature and some recommendations were developed based on these results.
Keywords: Principal; Management styles; Organizational justice; Job satisfaction; Burnout